The dynamics of commercialization of fruits in the community of Cochahuayco opportunities and challenges for peasant family farming - González Farroñay, Zoila Irene (2021)
The objective of the study was to identify the dynamics of fruit marketing in the community of Cochahuayco: opportunities and challenges for farming, peasant family economy. The study considers a sector of the rural population excluded and where the State is absent, to enhance the capacities of the population from a technical and credit point of view. However, for them it is a challenge and they use strategies that allow them to sustain themselves with the production of their fruits, the same ones that transform them into derivatives and go to consumers' tables; but not in the intensity that they wanted. The research was qualitative, exploratory and descriptive. 22 community members were selected, where 3 elected managers were considered, for presenting indicators of a constant struggle in the face of the challenges that are presented to them to market their products. Before applying the interview, a Focus Group applied to social actors was carried out to reconstruct the conceptions and experiences of the situation studied, this meeting was held in 2019 and this data has been collected, because with the It has not been possible to travel to the scene of the pandemic, some data has been validated through cell phone calls. The result allowed us to identify three forms of marketing dynamics: 1. Indirect-Long Marketing, 2. Commercialization Indirect – Short and 3. Direct Marketing - Consumer, very frequent in their agricultural activities, this does not allow them to boost marketing.